eCM 2012
DOI: 10.22203/ecm.v023a06
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating pTGF-β1/calcium phosphate nanoparticles with fibronectin into 3-dimensional collagen/chitosan scaffolds: Efficient, sustained gene delivery to stem cells for chondrogenic differentiation

Abstract: The objective of this study was to prepare a 3-dimensional nanoparticle gene delivery system (3D-NGDS) based on collagen/chitosan scaffolds, in which plasmid transforming growth factor beta 1 (TGF-β1)/calcium phosphate nanoparticles mixed with fibronectin (FN) were used to transfect mesenchymal stem cells (MSCs). Scanning electron microscopy was used to characterise the microstructure of 3-dimensional collagen/chitosan scaffolds. An analysis performed to quantify the TGF-1 concentrations in MSC cultures revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…The free amine groups on the chitosan molecule allow it to be crosslinked with the same agents as used for protein matrices (Reves et al, 2013;Wang and Stegemann, 2011), which can increase its mechanical strength and resistance to degradation. In addition, the positive charge on the chitosan molecule allows the material to be used for drug and gene delivery directly from the scaffold (Cao et al, 2012b;Goncalves et al, 2012).…”
Section: Natural Scaffoldsmentioning
confidence: 99%
“…The free amine groups on the chitosan molecule allow it to be crosslinked with the same agents as used for protein matrices (Reves et al, 2013;Wang and Stegemann, 2011), which can increase its mechanical strength and resistance to degradation. In addition, the positive charge on the chitosan molecule allows the material to be used for drug and gene delivery directly from the scaffold (Cao et al, 2012b;Goncalves et al, 2012).…”
Section: Natural Scaffoldsmentioning
confidence: 99%
“…Nanoparticles have been employed to deliver growth factors/genes into MSCs to manipulate their differentiation [17, 18]. They have also been used as contrast agents/nanoprobes for stem cell tracking [19, 20] to locate the site of stem cell activity, and determine the efficacy of the therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The above results indicate that the CMs had a slow degradation rate and poor adhesiveness to hAMSCs, which was not beneficial to cell proliferation leading to a weakness in biological activity. The results also suggested that CCMs and GCMs were favorable to the development of the cells and played a certain role in promoting hAM-SCs growth [50]. From the above results it is possible to state that the proliferation rate of hAMSCs grown on the CCMs and GCMs are better compared with the cells grown on Petri dishes.…”
Section: Growth Of Hamscs Cultured On Porous Chitosan Microspheresmentioning
confidence: 67%